Strategi Kepala Madrasah dalam Pengelolaan Program Tahfidz Al-Qur’an di Pondok Pesantren Darul Arifin Jambi - Musdalifah Hasibuan; Fridiyanto Fridiyanto; Summiyani Summiyani (JMiE (Journal of Management in Education), 2025)
This study aims to analyze the strategies of the principal in managing the Tahfidz Al-Qur’an Program at Madrasah Aliyah Pondok Pesantren Darul Arifin Jambi. A qualitative research approach was employed, with data collected through observation, interviews, and documentation, and validated using triangulation techniques. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the principal’s strategies in managing the Tahfidz program encompass visionary planning, collaborative organizing, adaptive implementation based on students’ abilities, and continuous evaluation of memorization outcomes. The principal plays a crucial role in coordinating tahfidz instructors, structuring learning schedules, and ensuring program consistency. This study highlights that strategic leadership of the principal is a key determinant in ensuring the effectiveness and sustainability of the Tahfidz Al-Qur’an Program in pesantren-based madrasahs.